A local geoid in Dronning Maud Land - Eiken, Trond; Omang, Ove Christian Dahl; Øvstedal, Ola ([European Geosciences Union], 1999)
The main purpose of the present paper is to estimate the orthometric height of the GPS-station at Troll, Dronning Maud Land, Antarctica. Located at approximately 1300 m Troll has been connected to the GIANT-network, but it's orthometric height remains undetermined. A local geoid has been determined based on available gravity anomalies and vertical angle mesurements. Information about the ice-thickness has been included in the terrain model. Based on tidal measurements the mean sea level was determined in Jutulgryta, a rift zone in the Fimbulisen ice shelf. Several gravity- and GPS-stations were measured between the two points (Jutulgryta and Troll), a distance of approximately 100 km.
Keywords: Dronning Maud Land; NARE ekspedisjoner; Troll forskningsstasjon; geodesi; kartlegging

Below-surface ice melt on the coastal Antarctic ice sheet - Liston, Glen E; Winther, Jan-Gunnar; Bruland, Oddbjørn; Elverhøy, Hallgeir; Sand, Knut (Journal of Glaciology, 1999)
In the Jutulgryta area of Dronning Maud Land, Antarctica, subsurface melting of the ice sheet has been observed. The melting takes place during the summer months in blue-ice areas under conditions of below-freezing air and surface temperatures. Adjacent snow-covered regions, having the same meteorological and climatic conditions, experience little or no subsurface melting. To help explain and understand the observed melt-rate differences in the blue-ice and snow-covered areas, a physically based numerical model of the coupled atmosphere, radiation, snow and blue-ice system has been developed. The model comprises a heat-transfer equation which includes a spectrally dependent solar-radiation source term. The penetration of radiation into the snow and blue ice depends on the solar-radiation spectrum, the surface albedo and the snow and blue-ice grain-sizes and densities. In addition, the model uses a complete surface energy balance to define the surface boundary conditions. It is run over the full annual cycle, simulating temperature profiles and melting and freezing quantities throughout the summer and winter seasons. The model is driven and validated using field observations collected during the Norwegian Antarctic Research Expedition (NARE) 1996–97. The simulations suggest that the observed differences between subsurface snow and blue-ice melting can be explained largely by radiative and heat-transfer interactions resulting from differences in albedo, grain-size and density between the two mediums.
Keywords: Dronning Maud Land; NARE 1996/97; blåis; geofysikk; glasiologi; innlandsis

Foothold on Antarctica : the first international expedition (1949-1952) : through the eyes of its youngest member - Swithinbank, Charles (Book Guild, 1999)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Climate variables along a traverse line in Dronning Maud Land, East Antarctica - van den Broeke, Michiel R; Winther, Jan-Gunnar; Isaksson, Elisabeth; Pinglot, Jean Francis; Karlöf, Lars; Eiken, Trond; Louk, Conrads (Journal of Glaciology, 1999)
Temperature, density and accumulation data were obtained from shallow firn cores, drilled during an overland traverse through a previously unknown part of Dronning Maud Land, East Antarctica. The traverse area is characterised by high mountains that obstruct the ice flow, resulting in a sudden transition from the polar plateau to the coastal region. The spatial variations of potential temperature, near-surface firn density and accumulation suggest that katabatic winds are active in this region. Proxy wind data derived from firn-density profiles confirm that annual mean wind speed is strongly related to the magnitude of the surface slope. The high elevation of the ice sheet south of the mountains makes for a dry, cold climate, in which mass loss owing to sublimation is small and erosion of snow by the wind has a potentially large impact on the surface mass balance. A simple katabatic-wind model is used to explain the variations of accumulation along the traverse line in terms of divergence/convergence of the local transport of drifting snow. The resulting wind- and snowdrift patterns are closely connected to the topography of the ice sheet: ridges are especially sensitive to erosion, while ice streams and other depressions act as collectors of drifting snow.
Keywords: Dronning Maud Land; NARE 1996/97; fysisk geografi; glasiologi; klimatologi; meteorologi

Noruega y las regiones polares - Hansson, Rasmus (Real Ministerio Noruego de Asuntos Exteriores, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norvegija i poljarnye rajony - Hansson, Rasmus (Izdano Ministerstvom inostrannych del Norvegii, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norwegen und die Polargebiete - Hansson, Rasmus (Kgl. Norwegisches Ministerium für Auswärtige Angelegenheiten, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Den norske antarktisekspedisjonen (NARE) 1996/97 - Haugland, Jan Erling (Polarboken, 1998)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1996/97; logistikk

Spatial variability of snow chemistry in western Dronning Maud Land, Antarctica - Stenberg, Malin; Isaksson, Elisabeth; Hansson, Margareta; Karlen, Wibjörn; Mayewski, Paul A.; Twickler, Mark S.; Whitlow, Sallie I.; Gundestrup, Niels (Annals of Glaciology, 1998)
During the austral summer of 1993-94 a number of 1-2 m deep snow pits were sampled in connection with firn-coring in western Dronning Maud Land, Antarctica. The traverse went from 800 to about 3000 m a.s.l. upon the high-altitude plateau. Profiles of cations (Na+, K+, Mg2+, Ca2+), anions (Cl−, NO3-, SO42- , CH3SO3−) and stable oxygen isotopes (δ18O) from 11 snow pils are presented here. Close to the coast 2 m of snow accumulates in about 2-3 years, whilst at sites on the high-altitude plateau 2 m of snow accumulates in 10—14 years. The spatial variation in ion concentrations shows that the ions can be divided into two groups, one with sea-salt elements and methane sulfonate and the other with nitrate and sulfate. For the sca-salt elements and methane sulfonate the concentrations decrease with increasing altitude and increasing distance from the coast, as well as with decreasing temperature and decreasing accumulation rate. For nitrate and sulfate the concentrations are constant or increase with respect to these parameters. This pattern suggests that the sources for sca-salt elements and methane sulfonate are local, whereas the sources for nitrate and sulfate are a mixture of local and long-range transport.
Keywords: Dronning Maud Land; geofysikk; geokjemi; glasiologi; iskjerner; meteorologi

Den norske antarktisekspedisjonen 1996/97: forskningsaktiviteter - Winther, Jan-Gunnar (Polarboken, 1998)
Keywords: Dronning Maud Land; forsking; klima

Nordic EPICA Dronning Maud Land pre site survey 1996/97: preliminary results from shallow ice core analysis - Winther, Jan-Gunnar; van den Broeke, Michiel R; Karlöf, Lars (Filchner-Ronne Ice Shelf Programme. Report, 1997)
Keywords: Dronning Maud Land; glasiologi; iskjerner

A force-balance study of ice flow and basal conditions of Jutulstraumen, Antarctica - Høydal, Øyvind Armand (Journal of Glaciology, 1996)
Stresses and velocities at depth are calculated across Jutulstraumen, an ice stream in Dronning Maud Land, draining about 1% of the Antarctic ice sheet. The force-balance study is based on data from kinematic GPS measurements on three strain nets, each consisting of 3 × 3 stakes. The maximum measured velocity is 443 m a−1 and the velocity variation over short distances is large compared with studied ice streams in West Antarctica. The surface topography together with the measured velocities across the profile indicate that the bottom topography has a great influence on the flow direction, even where the ice thickness is more than 2000 m. The basal shear stresses are calculated as 180, 227 and 146 kPa in the three Strain nets, while the corresponding driving stresses are 180, 122 and 111 kPa (±5%). The heat produced by sliding and internal deformation is sufficient to keep the base at the pressure-melting point. The annual basal melting is estimated to be about 60 mm. Investigations on the effect of temperature softening show that the flow parameter’s influence on the effective strain rate is more important than the flow parameter’s direct softening in the flow low alone. The mass flow calculated by the force-balance method is between 87 and 96% of pure plug flow and total discharge is calculated to be 13.3 ± 10 km3a-1.
Keywords: Dronning Maud Land; glasiologi; innlandsis; isstrøm

Mites collected in Heimefrontfjella and Vestfjella (Dronning Maud Land, Antarctica) - Thor, Göran (Fauna norvegica. Serie B, 1996)
Keywords: Dronning Maud Land; dyr; midder; zoologi

Melting, runoff and the formation of frozen lakes in a mixed snow and blue-ice field in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar; Elvehøy, Hallgeir; Bøggild, Carl Egede; Sand, Knut; Liston, Glen (Journal of Glaciology, 1996)
Large-scale melting phenomena such as meltwater drainage channels and meltwater accumulation basins of frozen lakes were surveyed on the land ice mass in Jutulgryta, Dronning Maud Land, Antarctica, during the Norwegian Antarctic Research Expedition in 1989–90 (NARE 1989–90). The largest frozen lake that was observed was close to 1 km in width. These melting features were also detected in a Landsat Thematic Mapper image recorded on 12 February 1990. Then, during NARE 1993–94, a 5year glaciological programme was started in this area. In spite of negative air temperatures and the presence of a frozen ice surface, sub-surface melting and runoff were found within the uppermost metre in blue-ice fields. The sub-surface melting is a consequence of solar radiative penetration and absorption within the ice, i.e. the “solid-state-greenhouse effect”. Temperatures in blue ice were about 6°C higher than for snow. Internal melt and meltwater transport were observed throughout the 1 month of measurements. The conditions for active melting in Jutulgryta are probably marginal. A slight increase of air temperatures can result in more “classical” surface melting, whereas a cooling may disable sub-surface melting. Studies of how the extent and characteristics of the melting features change with time can be particularly valuable as indicators of climate change. This ongoing programme clearly identifies the importance of analyzing how these melting features originate, of mapping their present areal distribution, of determining how sensitive they are to climate change and of Studying changes in the past and possible changes in the future.
Keywords: Dronning Maud Land; NARE 1989/90; NARE 1993/94; blåis; fjernanalyse; glasiologi; klimaendringer; satellitteknologi

Plans for the EPICA DML pre site survey 96/97 - Winther, Jan-Gunnar; van den Broeke, Michiel (Filchner-Ronne Ice Shelf Programme. Report, 1996)
Keywords: Dronning Maud Land; glasiologi

Sub-surface melting in blue-ice fields in Dronning Maud Land, Antarctica: observations and modelling - Bøggild, Carl Egede; Winther, Jan-Gunnar; Sand, Knut; Elvehøy, Hallgeir (Annals of Glaciology, 1995)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi; observasjoner

Antarktispetrellen: Sydishavets miljøbarometer - Lorentsen, Svein-Håkon (Natur, 1995)
Keywords: Dronning Maud Land; zoologi

Nordic contributions to EPICA Dronning Maud Land (DML) site survey - Winther, Jan-Gunnar (Filchner-Ronne Ice Shelf Programme. Report, 1995)
Keywords: Dronning Maud Land; glasiologi

High resolution climatic information from short firn cores, western Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn (Climatic Change, 1994)
In this paper a detailed record of major ions from a 20 m deep firn core from Amundsenisen, western Dronning Maud Land, Antarctica, is presented. The core was drilled at 75° S, 2° E (2900 m a.s.l.) during austral summer 1991/92. The following ions were measured at 3 cm resolution: Na+, Mg2+, Ca2+, Cl−, NO3−, S04 2− and CH3SO3H (MSA). The core was dated back to 1865 using a combination of chemical records and volcanic reference horizons. The volcanic eruptions identified in this core are Mount Ngauruhoe, New Zealand (1974–75), Mount Agung, Indonesia (1963), Azul, Argentina (1932), and a broad peak that corresponds in time toTarawera, New Zealand (1886), Falcon Island, South Shetlands, Southern Ocean (1885), and Krakatau, Indonesia (1883). There are no trends in any of the ion records, but the annual to decadal changes are large. The mean concentrations of the measured ions are in agreement with those from other high-altitude cores from the Antarctic plateau. At this core site there may be a correspondence between peaks in the MSA record and major El Niño–Southern Oscillation events.
Keywords: Dronning Maud Land; glasiologi; kjemi; klima

Antarktis - den siste villmark - Lorentsen, Svein-Håkon (NINA-Nytt, 1994)
Keywords: Dronning Maud Land; ekspedisjoner; forskning

Digestibility of krill (Euphausia superba and Thysanoessa sp.) in minke whales (Balaenoptera acutorostrata) and crabeater seals (Lobodon carcinophagus) - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (British Journal of Nutrition, 1994)
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

A bibliography of terrestrial biological research in Dronning Maud Land, Antarctica - Newton, I P; Cooper, J; Mehlum, Fridtjof; Thor, Göran (South African Journal of Antarctic Research, 1994)
A bibliography of terrestrial biological research in Dronning Maud Land, Antarctica, of 388 titles from 1954 to 1994 is provided as an aid to researchers working in the region.
Keywords: Dronning Maud Land; bibliografi; biologi

Resource limitation in a long-lived seabird, the Antarctic petrel Thalassoica antarctica: a twining experiment - Andersen, Reidar; Sæther, Bernt-Erik; Pedersen, Hans Christian (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1993)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

The Norwegian-British-Swedish Antarctic expedition 1949-1952 - Liljequist, Gösta H (High latitudes : a history of Swedish polar travels and research, 1993)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Documentation of the demography and population monitoring systems for Antarctic Petrels at Svarthamaren, Dronning Maud Land - Lorentsen, Svein-Håkon; Røv, Nils; Bangjord, Georg (Norsk institutt for naturforskning, 1993)
During the Norwegian Antarctic Research Expedition 1991/92, four 9 x 15 m squares for long-term demographic studies and 201 study plots for population monitoring of Antarctic Petrels Thalassatca anlarctica were established at Svarthamaren (71" 53' S, 5' 10' E), Dronning Maud Land. This report details their geographical location at Svarthamaren.
Keywords: Dronning Maud Land; NARE 1991/92; antarktispetrell; bestandsovervåking; fugler; ornitologi; zoologi

Digestibility of krill in crabeater seals and minke whales - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (1993)
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

Satellite tracking of crabeater seals off Queen Maud Land in Antarctica - Nordøy, Erling S; Folkow, Lars P; Blix, Arnoldus Schytte (1993)
Keywords: Dronning Maud Land; satellitt; seler; telemetri; zoologi

Studies of snow surface characteristics by Landsat TM in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Annals of Glaciology, 1993)
Keywords: Dronning Maud Land; glasiologi; satellittbilder

Studies through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Filchner-Ronne Ice Shelf Programme. Report, 1992)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis; oseanografi

Den norske antarktisekspedisjonen 1989-90 : medisinsk beredskap, arbeid og forskning - Bendiksen, Fredrik S; Molvær, Otto Inge; Reitehaug, Per-Ivar (Tidsskrift for den Norske Laegeforening, 1991)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; medisin; psykologi

Aspects of the breeding biology of the Antarctic Petrel Thalassoica antarctica and the krill requirement of the chicks, at Svarthamaren in Mühlig-Hofmanfjella, Dronning Maud Land - Haftorn, Svein; Bech, Claus; Mehlum, Fridtjof (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; krill; ornitologi; zoologi

Notes on the south polar skua Catharacta Maccormicki breeding at Svarthamaren in Mühlig-Hofmannfjella, Dronning Maud Land - Haftorn, Svein; Bech, Claus; Mehlum, Fridtjof (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

The density of breeding and non-breeding Antarctic petrels at Svarthamaren, Dronning Maud Land, 1990 - Røv, Nils (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Glaciologic and oceanographic studies on Fimbulisen during NARE 1989/90 - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Filchner-Ronne Ice Shelf Programme. Report, 1990)
Keywords: Dronning Maud Land; Sørishavet; ekspedisjoner; glasiologi; isbrem; oseanografi

Investigating Climate Change by Digital Analysis of Blue Ice Extent on Satellite Images of Antarctica - Orheim, Olav; Lucchitta, Baerbel (Annals of Glaciology, 1990)
Keywords: Dronning Maud Land; glasiologi; klimaendringer; satellitt; telemetri

lnvestigating climate change by digital analysis of satellite imagery of blue ice extent in Antarctica - Orheim, Olav; Luchitta, Baerbel (Annals of Glaciology, 1990)
Landsat-5 Thematic Mapper (TM) and SPOT data collected two years apart from an identical area of Dronning (Queen) Maud Land, Antarctica, have been analyzed to detect variations in surface features that may signal climatic change, and to establish a technique that readily identifies such changes. We found that selective principal component analysis (Chavez and Kwarteng 1989), on band ratios of near-IR/green, highlights changes in blue ice areas. The formation and preservation of blue ice is poorly understood, but we suggest that it generally takes longer to increase a blue ice area than to decrease it, and that blue ice extent is most sensitive to changes in accumulation rate. The investigated blue ice area shows a decrease in extent over the two-year period caused by incursion of snow that probably resulted from an increase in accumulation rate. Comparison of two TM images collected 18 days apart shows that transitory snow drifts have little effect on blue ice extent.
Keywords: Dronning Maud Land; glasiologi; klima

Bibliographia Phytosociologica. Norwegian possessions in the polar regions - Sunding, Per (Excerpta botanica, Sectio B, 1990)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; bibliografi; botanikk; polarområdene